A responsabilidade empresarial prevista no art. 931 do Código Civil de 2002 aplicada à progressiva inclusão de nanotecnologia no setor de ar condicionado automotivo : uma proposta para aplicação do princípio da precaução e gestão do risco inerente ao uso e descarte de materiais nanoestruturados - Cassali, Nina Koja (Universidade do Vale do Rio dos Sinos, 2017)
This research deals with nanotechnology and its possible implications in the field of civil liability attributed to entrepreneurs and business companies by the Civil Code of 2002, as well as its resulting in the society. The lack of regulations related to nanotechnology and the high probability of risks that it represents, together with the guidelines imposed by article 931 of the current CC, gave rise to the proposal of elaboration of a framework based on the procedures to be adopted with the initial intention to resolve the Harmful repercussions of future accountability, but above all, of preserving human and environmental health. For this purpose, bibliographic research, data collection and analysis of international standards were used. The research concluded that nanotechnology-based products are part of a rapidly expanding reality in everyone's life. The lack of knowledge about the harmfulness of the engineered nanoparticles already present in the atmosphere depends on the basic reason why all stages of nanomaterials' life must be rigorously controlled and analyzed, especially in the face of their toxic potential, hindering their probable harms as much as possible , So that, without frustrating technological progress, there is the guarantee of the permanence of human life as we know it today. Based on these values, the risk management suggestion materialized in the proposed framework was elaborated.
Keywords: Nanotecnologia; Responsabilidade; Empresas; Ar condicionado; Risco; Nanotechnology; Responsibility; Companies; Air conditioning; Risk; ACCNPQ::Ciências Sociais Aplicadas::Direito